2012
DOI: 10.1021/am3017653
|View full text |Cite
|
Sign up to set email alerts
|

Interface-Induced Crystalline Ordering and Favorable Morphology for Efficient Annealing-Free Poly(3-hexylthiophene): Fullerene Derivative Solar Cells

Abstract: A simple approach to fabricate high-efficiency annealing-free poly(3-hexylthiophene): [6,6]-phenyl C(61)-butyric acid methyl ester (P3HT:PCBM) solar cells is reported by using p-type CuI to substitute PEDOT:PSS as anode buffer layer. It is found that the P3HT:PCBM blend films deposited on CuI surface show different orientation of crystalline P3HT domains and phase separation from those deposited on PEDOT:PSS surface. A nanoscale phase separation of P3HT and PCBM with domain sizes about 10-30 nm is formed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 46 publications
5
47
1
1
Order By: Relevance
“…In the spectral region associated to π-πn interactions, the model fit, based on a uniaxial anisotropic assumption, reveals reduced ordinary extinction (k o , in-plane electric field vector) and increasing extraordinary extinction (k e , out-of-plane) ( Figure S8d) when CuI is used instead of PEDOT:PSS, indicating more face-on π-stacking interactions in the presence of CuI. This is consistent with a more face-on arrangement of P3HT domains observed on vacuum-deposited CuI, as reported by Shao et al [31]. Despite the differences in packing, the performance boost is quite small, perhaps reinforcing the fact that polymer conformation with a BHJ layer is not as critical as in the case of vacuum-deposited small-molecule OPV systems; the role of the HTL is certainly more dramatic in the latter, where molecules adsorb and self-assemble from the CuI substrate over a period of minutes, whereas the bulk heterojunction forms from a solution of entangled high Mw polymer chains on the subsecond to second timescale [44,45].…”
Section: Discussion Of the Templating Effect Of Cui On The Solution-psupporting
confidence: 88%
See 2 more Smart Citations
“…In the spectral region associated to π-πn interactions, the model fit, based on a uniaxial anisotropic assumption, reveals reduced ordinary extinction (k o , in-plane electric field vector) and increasing extraordinary extinction (k e , out-of-plane) ( Figure S8d) when CuI is used instead of PEDOT:PSS, indicating more face-on π-stacking interactions in the presence of CuI. This is consistent with a more face-on arrangement of P3HT domains observed on vacuum-deposited CuI, as reported by Shao et al [31]. Despite the differences in packing, the performance boost is quite small, perhaps reinforcing the fact that polymer conformation with a BHJ layer is not as critical as in the case of vacuum-deposited small-molecule OPV systems; the role of the HTL is certainly more dramatic in the latter, where molecules adsorb and self-assemble from the CuI substrate over a period of minutes, whereas the bulk heterojunction forms from a solution of entangled high Mw polymer chains on the subsecond to second timescale [44,45].…”
Section: Discussion Of the Templating Effect Of Cui On The Solution-psupporting
confidence: 88%
“…In light of the previously reported ability of vacuumdeposited CuI to modulate and template the molecular conformation and crystalline texture of semicrystalline polymers P3HT and P42TA [31,33] as well as smallmolecule organic semiconductors ZnPc and CuPc, [28][29][30] we investigate in this section whether CuI can influence the molecular orientation and phase separation of the solutionprocessed bulk heterojunction layers presented herein by focusing mainly on changes to the structural and optical properties of the semi-crystalline P3HT phase in P3HT:PCBM blends. As a first control experiment, we have vacuumdeposited ZnPc thin films on top of the solution-processed PEDOT:PSS and CuI interlayers and confirm through XRD measurements ( Figure S9a) that ZnPc takes an edge-on orientation ZnPc on PEDOT:PSS, but not on solutionprocessed CuI, in agreement with previous studies showing a more face-on packing character on CuI [28,29].…”
Section: Discussion Of the Templating Effect Of Cui On The Solution-pmentioning
confidence: 99%
See 1 more Smart Citation
“…In devices made with donor poly(3-hexylthiophene-2,5-diyl) (P3HT) and acceptor [6,6]-phenyl C 61 -butyric acid methyl ester (PCBM) it is shown that 4-fold enhancement in PCE results from 10-30nm domains of phase-separated P3HT and PCBM on a CuI surface compared to devices less-ordered films prepared on PEDOT:PSS surfaces [19]. Thermal and solvent annealing of OPV films has also demonstrated increased ordering correlating with increased PCE [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…25 CuI has also been incorporated in organic light emitting diodes (OLEDs) 26 and organic solar cells. 22 For example, Shao et al 27 recently reported OPV cells (power conversion efficiency (PCE) % 3.1%) employing thermally evaporated CuI as HTL. CuI has also been used as a p-dopant in hole transporting layers for OPV 28 and hybrid perovskite solar cells.…”
mentioning
confidence: 99%